Structural variants of Fragaria vesca - Minto Odagiri (22680003) (2025)
This dataset contains the high-confidence structural variants (SVs) detected in Fragaria vesca accessions ‘Yellow Wonder’ and ‘Hawaii-4’. SVs were discovered by integrating genome assembly, long-read whole-genome sequencing (ONT) and short-read (Illumina) whole-genome sequencing of 'Yellow Wonder' with a three-caller consensus workflow (SVIM-asm v1.1, Sniffles v2.2, Manta v1.6) against 'Hawaii-4' reference genome. After quality filtering and manual curation, 776 non-redundant SVs (≥ 50 bp; insertions, deletions, inversions, translocations) were retained.